2009
DOI: 10.4238/vol8-3gmr605
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of green bean (Phaseolus vulgaris) genotypes from eastern Turkey

Abstract: ABSTRACT. Green bean genotypes collected from eastern Turkey were characterized using simple sequence repeat (SSR) markers and morphological traits. Among 12 SSR markers, 10 produced successful amplifications and revealed DNA polymorphisms that were subsequently used to assess genetic relatedness of the genotypes. Based on the number of alleles generated and the probability of identity values, the most informative SSR loci were PVGLND5, PVMEIG, PVag001, and PV-ag004. Probably, due to the inbreeding nature of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…The discriminating power for each locus was comparable or higher than that reported for the same SSR locus (GATS91, BM210, BM160, PVBR25, BM172, PVBR163) in previous Italian collection studies [47][48][49]. Furthermore, mean He across eight SSR loci was higher (0.70) in our collection compared to those observed in other studies carried out on Italian [9,35,[47][48][49] as well as European collections [37,[60][61][62]. The overall loci probability of identity (PI) and PIC values obtained in our study prove the ability of this SSR panel to distinguish among common bean landraces of Nebrodi Mountains.…”
Section: Discussionsupporting
confidence: 73%
“…The discriminating power for each locus was comparable or higher than that reported for the same SSR locus (GATS91, BM210, BM160, PVBR25, BM172, PVBR163) in previous Italian collection studies [47][48][49]. Furthermore, mean He across eight SSR loci was higher (0.70) in our collection compared to those observed in other studies carried out on Italian [9,35,[47][48][49] as well as European collections [37,[60][61][62]. The overall loci probability of identity (PI) and PIC values obtained in our study prove the ability of this SSR panel to distinguish among common bean landraces of Nebrodi Mountains.…”
Section: Discussionsupporting
confidence: 73%
“…In most cultivated plant species, higher mean heterozygosity (He) have been reported. Some of the mean heterozygosity reported for plants are 0.30 in soyabean [33]; 0.32 in common beans using AFLP markers [34]; 0.361 in green beans using SSR markers [35]; 0.444 for mung bean using SSR markers [36], 0.361 in tea using AFLP markers [37], 0.313 in rice using SSR markers [38] and 0.37 in wheat with SSR markers [39].…”
Section: Discussionmentioning
confidence: 99%
“…Northeast Anatolian region. Another study reported genetic diversity of 30 genotypes from two districts of Van province i.e., Ercis and Gevas [ 30 ], while Nemli et al [ 31 ] used iPBS markers for the characterization of the 67 Turkish common bean landraces, and, in their recent work, Nemli et al [ 32 ] used SNP markers for the determination of diversity in the Turkish common bean.…”
Section: Introductionmentioning
confidence: 99%